براعة الزّمخشري في وعظ المسلمين من خلال مقاماته: من منظور علم النّص = The excellence of Az Zamakhsyari in giving advice to Muslims in his Maqamat: in the perspective of textual analysis - Mohd Ismath, Nurul Hanilah; Abd Aziz, Abdul Hadi (University of Malaya, 2018)
This study aims to explore the elements of cohesion and coherence in analysing Zamakhshari’s Maqamat. The study also made use of traditional Arabic linguistic heritage – Al Balaghah Al ‘Arabiyyah - in its text analysis and its relevancy with western textual perspective in the framework of Zamakhsari’s Maqamat. The study concluded that Zamakhshari utilized cohesive devices such as continuity, reference, repetition, inclusion, substitution; he also used figurative tools in his Maqamat such as allegories, metaphors and imageries to persuade and influence readers. Therefore, the application of textuality is excellently applied by Zamakhshari in his works.